Animals - Pledger, Maurice; Davies, Valerie, 1948- (Silver Dolphin Books, 2014)
Young animal enthusiasts are invited to go wild in an auditory adventure that features pop-up panoramas comparing the sounds made by a wide variety of exotic animals.
Cover title.
Keywords: Animals -- Juvenile literature; Sound effects books -- Specimens; Pop-up books -- Specimens; Animals; Sound effects books; Pop-up books; Toy and movable books